Pandemic Uncertainty Perception, Unemployment Risk Perception, and Remigration Intention of Migrant Workers in China - Ai-xiang Zheng; Hai-bo Zhang (Migration Letters, 2023)
Presently, despite the World Health Organization’s declaration of the end to the global health emergency posed by the COVID-19 pandemic, research on the influence of the COVID-19 pandemic continues. Migrant workers constitute the majority of China’s migrant population. Although the impact of the pandemic on their livelihoods is clear, the impact of the pandemic on their remigration intention remains unclear. This study, utilizing a sample of 321 Chinese migrant workers, employs a multivariate regression approach to examine the mechanisms through which the perceived uncertainty of the pandemic influences their remigration intention. The results demonstrate that the increased uncertainty caused by the pandemic heightens their unemployment risk perception and unemployment risk perception increases their remigration intention. Furthermore, it was found that human capital can mitigate both of these effects. However, this study did not find a direct impact of pandemic uncertainty on their remigration intention. This study explores unemployment risk perception of migrant workers under the influence of a major crisis and its impact on their remigration intentions, thus making predictions about their migration psychology and behavior under such circumstances. This study further enhances the theoretical framework surrounding research on remigration intention of migrant workers.